PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN SISTEM REM SISWA KELAS XI TEKNIK KENDARAAN RINGAN SMK PIRI SLEMAN TAHUN AJARAN 2014/2015 - Yudhia Putra Wardana; Subagyo Subagyo (Jurnal Taman Vokasi, 2016)
Application Demonstration Method To Increase Activity And Result Of Study Subject Brake System Class XI Technical Light Vehicle  Student Of SMK PIRI Sleman School year 2014/2015. Thesis Education Course Mechanical Engineering Faculty of Teacher Training and Education Sciences Sarjanawiyata Tamansiswa University Yogyakarta in 2015.